Trends in recreational walking trail usage in Ireland during the COVID-19 pandemic: Implications for practice. (March 2023) - Power, Dylan; Lambe, Barry; Murphy, Niamh
Abstract: Despite its potential utility for the outdoor recreation sector, there is no centralised surveillance system for recreational walking trails in Ireland and thus trail usage in Ireland during the COVID-19 pandemic is unknown. This paper aims to report trends in footfall count data on Irish trails during the COVID-19 period and to triangulate findings with openly available mobility data. This descriptive study analysed changes in footfall counts gathered from passive infrared sensors on 33 of Ireland's recreational walking trails between January 2019 and December 2020. The relationship between Google Community Mobility Report (GCMR) data and footfall counts was analysed to corroborate trends in footfall data. Total footfall increased by 6% between 2019 and 2020 on trails included in this analysis. Notably, mean trail usage was between 26% and 47% higher in October–December 2020 than during the same period in 2019. A strong correlation between GCMR data from 'parks' and footfall count data was found. The conclusions of this study are twofold. Firstly, the COVID-19 pandemic increased trail usage in Ireland, especially on trails closer to urban areas and there is potential for this to be a lasting legacy. Secondly, combining multiple data sources can provide trail managers with more detailed representations of trail usage and currently these are not harmonised. Future research should examine ways to encourage sustained recreational walking trail use in new users and implement novel ways to coordinate datasets across systems to monitor visitors on Irish recreational walking trails. Management implications: This paper presents a number of implications for trail management teams to consider: Openly available datasets pertaining to mobility, such as Google Community Mobility Reports, can be utilised to corroborate data collected from footfall sensors in place on trails. Furthermore, there may be potential for Google Trends data to help trail management teams gauge interest in specific trails and parks during defined time frames. There is considerable potential to sustain the COVID-19 legacy of increased trail use, especially for trails closer to urban areas, through promotional campaigns and continued trail maintenance. There is a need to work across sectors and disciplines within the recreational walking system to identify potential data sources and opportunities for further data collection.